The impact of limb deficiency impairment on Para swimming performance - Hogarth, L.; Payton, C.; van de Vliet, P.; Burkett, B. (Journal of Sports Sciences, 2020)
Swimmers with limb deficiency are a core population within Para Swimming, accordingly this study examined the contribution of limb segments to race performance in these swimmers. Data were obtained for 174 male Para swimmers with limb deficiency. Ensemble partial least squares regression showed accurate predictions when using relative limb segment lengths to estimate Para swimmers` personal best race performances. The contribution of limb segments to performance in swim events was estimated using these regression models. The analysis found swim stroke and event distance to influence the contributions of limb segments to performance. For freestyle swim events, these changes were primarily due to the increased importance of the hand, and decreased importance of the foot and shank, as the distance of the event increased. When comparing swim strokes, higher importance of the thigh and shank in the 100 m breaststroke compared with other swim strokes confirms the separate SB class. Varied contributions of the hand, upper arm and foot suggest that freestyle could also be separated from backstroke and butterfly events to promote fairer classification. This study shows that swim stroke and event distance influence the activity limitation of Para swimmers with limb deficiency suggesting classification should account for these factors.